MODIFICATION OF ELEMENTARY SCHOOL MATHEMATICS QUESTIONS INTO CONTEXTUAL QUESTIONS BASED ON BENGKULU CULTURE - Khaliq, Saddam; Adi Asmara; Risnanosanti (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This research aims to develop a prototype of contextual elementary school mathematics problems based on Bengkulu culture by modifying seven conventional problems into authentic narratives that integrate local elements such as the renovation of the Jamik Mosque (mixed arithmetic), the average number of visitors to Soekarno's House (descriptive statistics), the area of ​​the Anggut Atas rembulan batik cloth (area measurement), the volume of the Seluma durian lempuk packaging (cube volume), the circumference of the Rafflesia Kepahiang fence (circumference of a circle), the symmetry of the Besurek batik nail niche motif (transformation geometry), and the remaining spices (fractions). The Define-Develop phase focused on reconstructing the Merdeka curriculum document without field testing, resulting in an instrument that maintains conceptual rigor while enhancing affective relevance in line with Realistic Mathematics Education. The prototype is ready for dissemination as an inclusive teaching material, with implications for teacher training and digital media for elementary school mathematics learning in Bengkulu. Penelitian ini bertujuan mengembangkan prototipe soal matematika kontekstual sekolah dasar berbasis budaya Bengkulu melalui modifikasi tujuh soal konvensional menjadi narasi autentik yang mengintegrasikan elemen lokal seperti renovasi Masjid Jamik (aritmetika campuran), rata-rata pengunjung Rumah Soekarno (statistik deskriptif), luas kain batik besurek rembulan Anggut Atas (pengukuran luas), volume kemasan lempuk durian Seluma (volume balok), keliling pagar Rafflesia Kepahiang (keliling lingkaran), simetri motif relung paku batik besurek (geometri transformasi), dan sisa bumbu pendap (pecahan). Tahap Define-Develop difokuskan pada rekonstruksi dokumen kurikulum Merdeka tanpa uji lapangan, menghasilkan instrumen yang mempertahankan rigor konseptual sambil meningkatkan relevansi afektif selaras dengan Realistic Mathematics Education. Prototipe siap diseminasi sebagai bahan ajar inklusif, dengan implikasi pelatihan guru dan media digital untuk pembelajaran matematika SD di Bengkulu.